PERWUJUDAN NILAI MORALITAS DALAM PEMILIHAN PRESIDEN 2019 YANG DEMOKRATIS DAN BERKEADILAN - Dimas Bima Setiyawan (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
Moral is an ethic inherent ain a human being. Formed trough verous diverse events that have been passed, one of wich is trough the role of religion. The importance of the role is broken down in the form of behavior of each individual in response to everything that is present in his life. Religion was reveald for justice, morality, mutual respect, and called for creating a peaceful order of live among fellow human beings. The importance of promoting morality based on religion will greatly affect the pattern of life carried out by every human being. one of them is responding to the upcoming 2019 preidential election. The values contained in it will certainly influence the realization of the five-year event to realize a democratic and justice election system.